Beyond Extremism: Muslim-Christian Dialogue in a Post-9/11 Era - Reynolds, Thomas (Théologiques, 2011)
Seeking to move beyond language of “extremism”, this article discusses some of the promises and perils of Muslim-Christian dialogue in an era after September 11, 2001. The author advocates for the public face of religion in secular societies, assesses several recent developments in Muslim-Christian engagements, and proposes steps for opening up a more fruitful contemporary collaboration between Muslims and Christians. Written from a Christian perspective, the article concludes by arguing for “dialogical openness” as a hopeful path toward interfaith mutuality.